The Effectiveness Of Using Think, Talk, Write (Ttw) InTeaching Writing Skill To The Seventh Grade Student OfMts N 2 Surakarta - Sholechah, Nuraini ridi, Nur Hidayat M.Pd (2017)
The objectives of research are: (1) To know the students' pre-test and post-test scores in writing skill in the experimental group (2) To know the student's pre-test and post-test scores in writing skill in control group (3)To knowthe significant difference score between the students who are taught by using Think Talk Write and who are taught using Guided writing (4)To know the effectiveness in eaching writing skill at third grade of MTs N 2 Surakarta. The research was conducted in the first semester of the seventh grade students of MTs N 2 Surakartain the academic year of 2015/2016. The sampling used was random sampling. The samples were two classes which consist of 34 students,class VII 1 as a experiment class and 34 students class VII 2 as the control class. The instrument used was test, the researcher used form of essay test. The result of the research reveals that: (1)the pre-test score in writing descriptive text of the experimental group were 2110 and the mean was 62.05. Meanwhile the post-test score of the tudents in experimental group were 2495 with the mean 73.38 (2) the pre-test score of thestudentsin control group were 2094 with the mean 61.58 and post-test score of in controlgroup were 2272 with the mean 66.82. (3) there is significant diference score in writing skill between the students taught by using Think Talk Write and students taught Guided Writing to the seventh grade student of MTs N 2 Surakarta (4) Think Talk Write is more effective to teach wriiting to seventh grade students of MTs N 2 Surakarta in academic 2015/2016.